Dependency of mesh size and loading history on crack propagation energy of cyclic ductile fracture model. (15th June 2019) - Jia, Liang-Jiu; Fujie, Wataru; Ikai, Toyoki; Yoshida, Soichiro; Ge, Hanbin
Highlights: Few studies on cracking simulation of welded steel joints under ultra-low-cycle fatigue loading conducted. Cracking simulation of the joints conducted using a cyclic ductile fracture model. Significant mesh size and loading history dependency found for the crack propagation energy. A method to mitigate mesh and loading history dependency effects proposed. The cracking behaviors of the joints in the simulations compare well with the experimental ones. Abstract: Ductile fracture is one of the main failure modes of metal structures, especially under ultra-low-cycle fatigue (ULCF) loading. To date, it is still difficult to accurately predict ULCF failure of welded steel structures. This paper aims to investigate mesh size and loading history dependency effects of a previously proposed cyclic ductile fracture model. The ductile fracture model is employed to simulate experimental results of welded T-joints under cyclic bending. A method to mitigate the mesh size and loading history dependency effects is proposed in this study, and is also employed to simulate the whole cracking processes of the specimens. The proposed method can predict the crack initiation with good accuracy, and there are still some deviations for the crack propagation simulation. In addition, it is found that the size dependency effect decreases rapidly as the characteristic length of the elements increases, and the loading history has a great effect on the fracture energy parameter in the cyclic ductile fracture model.